Modulation of Hedgehog Signaling by Kappa Opioids to Attenuate Osteoarthritis - Weber, Alexander E.; Jalali, Omid; Limfat, Sean; Shkhyan, Ruzanna; Van Der Horst, Robert; Lee, Siyoung; Lin, Yucheng; Li, Liangliang; Mayer, Erik N.; Wang, Liming; Liu, Nancy Q.; Petrigliano, Frank A.; et al. (Arthritis & rheumatology (Hoboken, N.J.), 2020)
Objective Inhibition of hedgehog (HH) signaling prevents cartilage degeneration and promotes repair in animal models of osteoarthritis (OA). This study, undertaken in OA models and in human OA articular cartilage, was designed to explore whether kappa opioid receptor (KOR) modulation via the inhibition of HH signaling may have therapeutic potential for achieving disease‐modifying activity in OA. Methods Primary human articular cartilage and synovial tissue samples from patients with knee OA undergoing total joint replacement and from healthy human subjects were obtained from the National Disease Research Interchange. For in vivo animal studies, a partial medial meniscectomy (PMM) model of knee OA in rats was used. A novel automated 3‐dimensional indentation tester (Mach‐1) was used to quantify the thickness and stiffness properties of the articular cartilage. Results Inhibition of HH signaling through KOR activation was achieved with a selective peptide agonist, JT09, which reduced HH signaling via the cAMP/CREB pathway in OA human articular chondrocytes (P = 0.002 for treated versus untreated OA chondrocytes). Moreover, JT09 markedly decreased matrix degeneration induced by an HH agonist, SAG, in pig articular chondrocytes and cartilage explants (P = 0.026 versus untreated controls). In vivo application of JT09 via intraarticular injection into the rat knee joint after PMM surgery significantly attenuated articular cartilage degeneration (60% improvement in the tibial plateau; P = 0.021 versus vehicle‐treated controls). In JT09‐treated rats, cartilage content, structure, and functional properties were largely maintained, and osteophyte formation was reduced by 70% (P = 0.005 versus vehicle‐treated controls). Conclusion The results of this study define a novel mechanism for the role of KOR in articular cartilage homeostasis and disease, providing a potential unifying mechanistic basis for the overlap in disease processes and features involving opioid and HH signaling. Moreover, this study identifies a potential novel therapeutic strategy in which KOR modulation can improve outcomes in patients with OA.